Polymorphism of prion protein gene (PRNP) in Nigerian sheep. Issue 1 (31st December 2023) - Adeola, Adeniyi C.; Bello, Semiu F.; Abdussamad, Abdussamad M.; Mark, Akanbi I.; Sanke, Oscar J.; Onoja, Anyebe B.; Nneji, Lotanna M.; Abdullahi, Nasiru; Olaogun, Sunday C.; Rogo, Lawal D.; Mangbon, Godwin F.; Pedro, Shamsudeen L.; et al.
ABSTRACT: Polymorphism of the prion protein gene ( PRNP ) gene determines an animal's susceptibility to scrapie. Three polymorphisms at codons 136, 154, and 171 have been linked to classical scrapie susceptibility, although many variants of PRNP have been reported. However, no study has investigated scrapie susceptibility in Nigerian sheep from the drier agro-climate zones. In this study, we aimed to identify PRNP polymorphism in nucleotide sequences of 126 Nigerian sheep by comparing them with public available studies on scrapie-affected sheep. Further, we deployed Polyphen-2, PROVEAN, and AMYCO analyses to determine the structure changes produced by the non-synonymous SNPs. Nineteen (19) SNPs were found in Nigerian sheep with 14 being non-synonymous. Interestingly, one novel SNP (T718C) was identified. There was a significant difference ( P  < 0.05) in the allele frequencies of PRNP codon 154 between sheep in Italy and Nigeria. Based on the prediction by Polyphen-2, R154H was probably damaging while H171Q was benign. Contrarily, all SNPs were neutral via PROVEAN analysis while two haplotypes (HYKK and HDKK) had similar amyloid propensity of PRNP with resistance haplotype in Nigerian sheep. Our study provides valuable information that could be possibly adopted in programs targeted at breeding for scrapie resistance in sheep from tropical regions.